Antiviral activity of selected IFN-beta stimulated genes - Kabrelian, Armig (Jihočeská univerzita, 2018)
The main aim of this thesis is to determine the possible antiviral activity of IFI6 and IFI27 genes in case of TBEV infection in DAOY cells. Both genes belong to the large family of interferon-stimulated genes and were previously shown to be highly up-regulated in DAOY cells treated with IFN-, which lead to the significant decrease of TBEV titres. To investigate the possible role of IFI6 and IFI27 in this effect, they were both cloned separately into mammalian expression vectors and their contribution to an anti-viral state in DAOY cells was elucidated, using an in vitro transient over-expression.
Antiviral activity of selected IFN-beta stimulated genes